The associations among nurse work engagement, job satisfaction, quality of care, and intent to leave: A national survey in the United States - Holly Wei; Leann Horsley; Yan Cao; Lisa M. Haddad; Katherine C. Hall; Roslyn Robinson; Margaret Powers; Debra Gay Anderson (Elsevier, 2023)
Objectives: Employee work engagement, job satisfaction, quality of care, and intent to leave are critical indicators for healthcare organizational performance. This study aimed to analyze the current state of nurses' work engagement and its factors to examine the associations among nurses' work engagement, job satisfaction, quality of care, and intent to leave in the United States (US). Methods: This is a quantitative descriptive cross-section design. Data were collected online from the US registered nurses from March to September 2022. Measures comprised the Utrecht Work Engagement Scale, the demographics, and questions regarding job satisfaction, perceived quality of care, and intent to leave. Results: Nine hundred nurses participated in the online survey. Among the participants, 79.2% reported holding a specialty certification, 59.4% scored high/very high on job satisfaction, 82.2% expressed high/very high on the perceived quality of nursing care, and 28.4% conveyed likely/very likely to leave in the following year. Nurses' work engagement was positively associated with nurses' job satisfaction and their perceived quality of care but negatively associated with intent to leave. More certified nurses reported high or very high job satisfaction than non-certified nurses. As for demographics, the linear regression analysis showed that nurses who were older, identified as White, and held doctorate degrees reported higher levels of work engagement in comparison to their counterparts. Conclusions: This study shows that nurses' work engagement is associated with their job satisfaction, perceived quality of care, and intent to leave. Nurses' work engagement in this study is lower than in other studies, especially before the COVID-19 pandemic, which may indicate a possible association with the COVID-19 impact. Because nurses' work engagement is significantly associated with job satisfaction, nurse leaders need to find ways to promote nurses' job satisfaction and retention.